Double-P flame retardant, epoxy composite material and application in IV-type hydrogen storage cylinder
By introducing bio-based double P flame retardant into epoxy resin and forming a network structure through mutual cross-linking, the problem that epoxy resin is difficult to take into account strength, toughness and flame retardant characteristics in type IV hydrogen storage cylinders is achieved. The mechanical properties and flame retardant properties of epoxy composite materials have been significantly improved.
Patent Information
- Application Number
- CN202510058385.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing epoxy resin for type IV hydrogen storage cylinders is difficult to take into account strength, toughness and flame retardant characteristics, which limits its application in high-pressure hydrogen storage cylinders.
A bio-based double P flame retardant is used to form a special network structure by crosslinking with epoxy resin to improve its mechanical properties and flame retardant properties. The preparation method of the flame retardant includes a multi-step reaction process, using specific raw materials and catalysts to form a double P flame retardant with high viscosity and excellent thermal responsiveness.
It significantly improves the bending strength, elongation of break, impact strength and flame retardant properties of the epoxy composite material. It is suitable for the wound layer material of Type IV hydrogen storage cylinders, enhancing the safety of the cylinders.
Smart Images

Figure CN119490531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame retardant materials, and in particular to a double P flame retardant, an epoxy composite material and applications in a type IV hydrogen storage cylinder. Background Art
[0002] As one of the most commonly used thermosetting materials in the world, epoxy resin (EP) is easily used in a wide range of fields such as aerospace, automobile manufacturing, adhesives and circuit packaging materials due to its high mechanical strength and transparency as well as excellent thermal and chemical stability. However, the brittleness and poor crack propagation resistance caused by the high degree of crosslinking of epoxy resin, as well as its high flammability caused by a large number of flammable groups, limit the scope of application of EP. It is generally believed that it is difficult to achieve the improvement of mechanical properties and flame retardant properties at the same time.
[0003] With the increasing demand for clean energy, high-pressure hydrogen storage technology has received widespread attention. As one of the main manufacturing materials for hydrogen cylinders, epoxy composites have become a research focus due to their excellent mechanical properties and chemical corrosion resistance. After decades of development, high-pressure hydrogen storage cylinders have completed multiple generations. Among them, Type IV high-pressure hydrogen storage cylinders with nylon as the inner liner and carbon fiber / epoxy resin composites as the winding layer have become the most mature production solution. However, Type IV hydrogen storage cylinders require the resin to have low curing temperature, short curing time, strong rigidity, good toughness and flame retardancy of the composite material. Existing commercial epoxy resins are difficult to apply to the wet winding process system of Type IV hydrogen storage cylinders.
[0004] The usual way to solve the above problems is to add functional flame retardants to the epoxy resin system to improve the comprehensive performance of EP. In addition, introducing the second phase into the epoxy resin matrix is also considered to be an effective means to improve the toughness of cured EP. However, the raw materials of additives are mostly petrochemical products, which have limited resources and contain harmful chemicals, which have a negative impact on the environment. Phosphorus-based flame retardants have attracted more and more attention due to their low toxicity, diverse structures, and high efficiency. However, the flame retardant efficiency of compounds containing a single phosphorus element is low. The DOPO structure can be used in combination with compounds containing nitrogen, sulfur, boron or silicon. In contrast, phosphorus-nitrogen synergistic flame retardants help to form an insulating multi-space sparse expanded carbon layer, which acts as a barrier to air, heat and pyrolysis products during thermal decomposition, and can have a good flame retardant effect. However, while the flame retardant properties of epoxy resin are improved after adding flame retardants, the mechanical properties of epoxy resin are usually sacrificed.
[0005] Therefore, how to simultaneously improve the strength, toughness and flame retardant properties of epoxy resin and comprehensively study the synergistic effects of these three are crucial to improving the safety of hydrogen storage cylinders. Summary of the invention
[0006] In order to solve the problem that epoxy resin used in existing Type IV hydrogen storage cylinders is difficult to achieve both strength, toughness and flame retardancy, the present invention proposes a double P flame retardant, an epoxy composite material and the application thereof in Type IV hydrogen storage cylinders.
[0007] The technical solution of the present invention is as follows: A bio-based double P flame retardant, the structural formula is as follows: ; In the formula, R1 is selected from , , , , , One of; R2 is selected from , , , , One of the following, wherein n1 is any integer from 1 to 16, and n2 is selected from 230, 400, 600, 1000 or 2000.
[0008] The present invention also provides a method for preparing the above-mentioned bio-based double P flame retardant, comprising the following steps: Step 1: dissolving raw material A and triethylamine in ethyl acetate, then adding diphenyl chlorophosphate dropwise at 0°C to 5°C under a nitrogen atmosphere, stirring for 30min to 60min, gradually warming the system to room temperature and continuing stirring for 12h to 24h, and then performing post-treatment to obtain the first intermediate; Step 2: dissolving the first intermediate obtained in step 1 in a solvent, then adding raw material B, and reflux reacting at 30°C to 90°C for 2h to 10h. After the reaction is completed, removing the solvent by rotary evaporation, and then vacuum drying at 50°C to 80°C for 12h to 24h to obtain a Schiff base intermediate; Step 3, dissolving the Schiff base intermediate in a solvent, then dropping DOPO under a nitrogen atmosphere, and reflux reacting at 50°C to 120°C for 8h to 20h. After the reaction, removing the solvent by rotary evaporation, and then vacuum drying at 50°C to 100°C for 12h to 24h to obtain a reactive bio-based double P flame retardant; Wherein, the raw material A is selected from one or a combination of at least two of vanillin, p-hydroxybenzaldehyde, 5-hydroxymethylfurfural, salicylaldehyde, protocatechualdehyde, and syringaldehyde; The raw material B is selected from one or a combination of at least two of Pramine 1074, diethylenetriamine, triethylenetetramine, 1,5-pentanediamine, 1,6-hexanediamine, polyetheramine D-230, polyetheramine D-400, polyetheramine D-600, polyetheramine D-1000, and polyetheramine D-2000.
[0009] Preferably, the post-treatment method includes: filtration, washing, drying and rotary evaporation.
[0010] Preferably, the solvent in step 2 is one or a combination of at least two of anhydrous ethanol, methanol, tetrahydrofuran, dichloromethane, chloroform, ethyl acetate, acetone, toluene, and 1,4-dioxane.
[0011] Preferably, the solvent in step three is one or a combination of at least two of methanol, anhydrous ethanol, acetone, toluene, 1,4-dioxane, and N,N-dimethylformamide.
[0012] The present invention also provides an epoxy composite material, wherein the raw materials include, by weight, 1-20 parts of the bio-based double P flame retardant according to claim 1, 100 parts of epoxy resin, and 25 parts of curing agent.
[0013] Preferably, the epoxy resin is bisphenol A epoxy resin, and the curing agent is 4,4'-diaminodiphenylmethane.
[0014] The preparation method of the epoxy composite material comprises the following steps: The bio-based double P flame retardant and epoxy resin are stirred and mixed at 70° C. to 120° C., and a uniform system is obtained and then vacuumed. When there are no bubbles in the mixture in the vacuum, a curing agent is added at 50° C. to 120° C. and mixed uniformly. Finally, the mixture is poured into a preheated mold for curing.
[0015] Preferably, the mold preheating temperature is 80°C~120°C, and the preheating time is 30min~90min; the curing process is specifically: after curing at 100°C~140°C for 60min~120min, adjust the temperature to 120°C~160°C, and then cure for 60min~150min.
[0016] The present invention also provides an application of the epoxy composite material, which is specifically used for preparing a winding layer of a type IV fully wound hydrogen storage cylinder.
[0017] Compared with the prior art, the specific beneficial effects of the present invention are: The present invention synthesizes a double P flame retardant with green, environmentally friendly and renewable bio-based raw materials. The double P flame retardant has high viscosity at room temperature, shows excellent fluidity after heating, and has good thermal responsiveness and processing performance. Since the -NH group in the flame retardant in the composite material can participate in the curing reaction of the epoxy resin, it cross-links with the epoxy resin to form a special network structure, which greatly improves the compatibility of the flame retardant with the epoxy resin. The main chain aromatic ring and phosphorus-containing aromatic side chain in the flame retardant serve as rigid groups, and when the composite material is subjected to external force, the flexible chain can withstand and disperse stress, increase the free space of activity, and thus increase toughness. The rigid group cooperates with the flexible chain, and its unique rigid-flexible combination structure gives the epoxy resin matrix excellent mechanical properties. In addition, the double phosphorus structure in the flame retardant and the synergistic effect between nitrogen and phosphorus elements achieve a good flame retardant effect. The flame retardant decomposes into some phosphorus-based groups, such as phosphoric acid or polyphosphoric acid compounds, to catalyze the molecular chain segments into coke. At the same time, nitrogen-based gases are released into the gas phase to dilute combustible volatiles, resulting in the termination of combustion and preventing the degradation and combustion of the internal matrix, thereby making the epoxy composite material have excellent flame retardant properties.
[0018] The reaction process of the invention is easy to operate and the preparation method is simple, which not only provides a new idea for expanding the application of epoxy resin in the field of high-performance materials, but also provides a more suitable winding layer material for hydrogen energy, especially type IV hydrogen storage cylinders, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the infrared spectrum of the products at each stage in Example 1; Figure 2 1-3 and 1-2 are tensile stress-strain curves of the epoxy composite materials; Figure 3 The figure is a comparison chart of the bending strength and bending modulus of the epoxy composite materials in Examples 1-3 and Comparative Examples 1-2; Figure 4 It is a comparison chart of the impact strength of the epoxy composite materials in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0020] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0021] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0022] Example 1 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added dropwise to the above solution under a nitrogen atmosphere at 0°C to 5°C. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the mixture was filtered to remove the generated salt, the filtrate was washed with deionized water and brine solution in turn, the organic phase was dried with anhydrous magnesium sulfate for 12 hours, and then the ethyl acetate was removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate VD.
[0023] (2) In a three-necked round-bottom flask, VD was dissolved in anhydrous ethanol, and then Pramine 1074 was added to the above solution, and refluxed at 70°C for 4 h. The solvent was removed by rotary evaporation, and then vacuum dried at 70°C for 24 h to obtain the desired Schiff base intermediate VDP.
[0024] (3) In a three-necked round-bottom flask, the VDP obtained above was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation and then vacuum dried at 80°C for 24 h to obtain the desired flame retardant VDPD.
[0025] The above reaction route is as follows: .
[0026] The infrared spectra of the products in the above stages are shown in Figure 1 , in the VD spectrum, at 1700 cm -1 The peak at 1645cm belongs to the stretching vibration of the aldehyde group C=O, and no characteristic peak of -OH is detected, indicating the successful synthesis of VD. In the VDP spectrum, the C=O peak in VP disappears, and the peak at 1645cm -1 A new stretching vibration belonging to the Schiff base C=N appeared at 1645 cm -1 The C=N peak at 2435cm in DOPO -1 The PH peak at 1510 cm −1 A new peak belonging to the -NH group appeared at 1234 cm -1 and 926cm -1 The above results all indicate the successful synthesis of the final product VDPD, which proves that the reaction proceeds smoothly according to the above route.
[0027] (4) Add 10 parts of the prepared VDPD to 100 parts of bisphenol A epoxy resin, stir evenly at 90°C and evacuate. When there are no bubbles in the mixture in the vacuum, add 25 parts of molten 4,4-diaminodiphenylmethane (DDM) as a curing agent at 105°C and mix evenly. Pour the mixed sample into the mold quickly, preheat the mold at 110°C for 30 min, cure at 120°C for 2h, adjust the temperature to 150°C, and post-cure for 2h to obtain the epoxy composite material 10VDPD.
[0028] Example 2 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added dropwise to the above solution under a nitrogen atmosphere at 0°C to 5°C. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the mixture was filtered to remove the generated salt, the filtrate was washed with deionized water and brine solution in turn, the organic phase was dried with anhydrous magnesium sulfate for 12 hours, and then the ethyl acetate was removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate VD.
[0029] (2) In a three-necked round-bottom flask, VD was dissolved in anhydrous ethanol, and then Pramine 1074 was added to the above solution, and refluxed at 70°C for 4 h. The solvent was removed by rotary evaporation, and then vacuum dried at 70°C for 24 h to obtain the desired Schiff base intermediate VDP.
[0030] (3) In a three-necked round-bottom flask, the VDP obtained above was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation and then vacuum dried at 80°C for 24 h to obtain the desired flame retardant VDPD.
[0031] (4) Add 15 parts of the prepared VDPD to 100 parts of bisphenol A epoxy resin, stir evenly at 90°C and evacuate. When there are no bubbles in the mixture in the vacuum, add 25 parts of molten 4,4-diaminodiphenylmethane (DDM) as a curing agent at 105°C and mix evenly. Pour the mixed sample into the mold quickly, preheat the mold at 110°C for 30 min, cure at 120°C for 2h, adjust the temperature to 150°C, and post-cure for 2h to obtain the epoxy composite material 15VDPD.
[0032] Example 3 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added to the above solution at 0-5°C under a nitrogen atmosphere. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the reaction, the mixture was filtered to remove the generated salt. The resulting filtrate was then washed with deionized water and brine solution in turn, and the organic phase was dried with anhydrous magnesium sulfate for 12 hours. The ethyl acetate was then removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate VD.
[0033] (2) In a three-necked round-bottom flask, VD was dissolved in anhydrous ethanol. Subsequently, Pramine 1074 was added to the above solution and refluxed at 70°C for 4 h. The solvent was removed by rotary evaporation and then vacuum dried at 70°C for 24 h to obtain the desired Schiff base intermediate VDP.
[0034] (3) In a three-necked round-bottom flask, the VDP obtained above was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation and then vacuum dried at 80°C for 24 h to obtain the desired flame retardant VDPD.
[0035] (4) Add 20 parts of the prepared VDPD to 100 parts of bisphenol A epoxy resin, stir evenly at 90°C and evacuate. When there are no bubbles in the mixture in the vacuum, add 25 parts of molten 4,4-diaminodiphenylmethane (DDM) as a curing agent at 105°C and mix evenly. Pour the mixed sample into the mold quickly, preheat the mold at 110°C for 30 min, cure at 120°C for 2h, adjust the temperature to 150°C, and post-cure for 2h to obtain the epoxy composite material 20VDPD.
[0036] Example 4 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added to the above solution at 0-5°C under a nitrogen atmosphere. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the reaction, the mixture was filtered to remove the generated salt. The resulting filtrate was then washed with deionized water and brine solution in turn, and the organic phase was dried with anhydrous magnesium sulfate for 12 hours. The ethyl acetate was then removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate.
[0037] (2) In a three-necked round-bottom flask, the product obtained in (1) was dissolved in anhydrous ethanol. Subsequently, 1,6-hexanediamine was added to the above solution and refluxed at 50°C for 5 h. The solvent was removed by rotary evaporation and then vacuum dried at 60°C for 24 h to obtain the desired Schiff base intermediate.
[0038] (3) In a three-necked round-bottom flask, the Schiff base obtained in (2) was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere, and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation, and then vacuum dried at 80°C for 24 h to obtain the desired target product.
[0039] (4) 15 parts of the target product prepared above were added to 100 parts of bisphenol A epoxy resin, stirred at 90°C and then vacuumed. When there were no bubbles in the mixture in the vacuum, 25 parts of molten 4,4-diaminodiphenylmethane (DDM) were added as a curing agent at 105°C and mixed evenly. The mixed sample was quickly poured into a mold, the mold was preheated at 110°C for 30 minutes, cured at 120°C for 2 hours, and then the temperature was adjusted to 150°C and post-cured for 2 hours to obtain an epoxy composite material.
[0040] Example 5 (1) In a three-necked round-bottom flask, p-hydroxybenzaldehyde and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added to the above solution at 0-5°C under a nitrogen atmosphere. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the reaction, the mixture was filtered to remove the generated salt. The resulting filtrate was then washed with deionized water and brine solution in sequence, and the organic phase was dried with anhydrous magnesium sulfate for 12 hours. The ethyl acetate was then removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate.
[0041] (2) In a three-necked round-bottom flask, the product obtained in (1) was dissolved in anhydrous ethanol. Subsequently, Pramine 1074 was added to the above solution and refluxed at 70°C for 4 h. The solvent was removed by rotary evaporation and then vacuum dried at 70°C for 24 h to obtain the desired Schiff base intermediate.
[0042] (3) In a three-necked round-bottom flask, the Schiff base obtained in (2) was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere, and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation, and then vacuum dried at 80°C for 24 h to obtain the desired target product.
[0043] (4) 15 parts of the prepared target product were added to 100 parts of bisphenol A epoxy resin, stirred at 90°C and then vacuumed. When there were no bubbles in the mixture in the vacuum, 25 parts of molten 4,4-diaminodiphenylmethane (DDM) were added as a curing agent at 105°C and mixed evenly. The mixed sample was quickly poured into a mold, the mold was preheated at 110°C for 30 minutes, cured at 120°C for 2 hours, and then the temperature was adjusted to 150°C and post-cured for 2 hours to obtain an epoxy composite material.
[0044] Example 6 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added to the above solution at 0-5°C under a nitrogen atmosphere. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the reaction, the mixture was filtered to remove the generated salt. The resulting filtrate was then washed with deionized water and brine solution in turn, and the organic phase was dried with anhydrous magnesium sulfate for 12 hours. The ethyl acetate was then removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate.
[0045] (2) In a three-necked round-bottom flask, the product obtained in (1) was dissolved in anhydrous ethanol. Subsequently, polyetheramine was added to the above solution and refluxed at 60°C for 5 h. The solvent was removed by rotary evaporation and then vacuum dried at 60°C for 24 h to obtain the desired Schiff base intermediate.
[0046] (3) In a three-necked round-bottom flask, the Schiff base obtained in (2) was dissolved in anhydrous ethanol. Subsequently, DOPO was added dropwise to the above solution under a nitrogen atmosphere, and refluxed at 85°C for 20 h. The solvent was removed by rotary evaporation, and then vacuum dried at 80°C for 24 h to obtain the desired target product.
[0047] (4) 15 parts of the prepared target product were added to 100 parts of bisphenol A epoxy resin, stirred at 90°C and then vacuumed. When there were no bubbles in the mixture in the vacuum, 25 parts of molten 4,4-diaminodiphenylmethane (DDM) were added as a curing agent at 105°C and mixed evenly. The mixed sample was quickly poured into a mold, the mold was preheated at 110°C for 30 minutes, cured at 120°C for 2 hours, and then the temperature was adjusted to 150°C and post-cured for 2 hours to obtain an epoxy composite material.
[0048] Comparative Example 1 At 105°C, 25 parts of molten 4,4-diaminodiphenylmethane (DDM) were added as a curing agent to 100 parts of bisphenol A epoxy resin. After stirring evenly, the mixed sample was quickly poured into the mold. The mold was preheated at 110°C for 30 min. After curing at 120°C for 2h, the temperature was adjusted to 150°C and post-cured for 2h to obtain EP epoxy resin material.
[0049] Comparative Example 2 (1) In a three-necked round-bottom flask, vanillin and catalyst triethylamine were dissolved in ethyl acetate. Subsequently, diphenyl chlorophosphate was slowly added to the above solution at 0-5°C under a nitrogen atmosphere. After stirring for 30 minutes, the system was gradually warmed to room temperature and stirred for another 16 hours. After the reaction, the mixture was filtered to remove the generated salt. The resulting filtrate was then washed with deionized water and brine solution in turn, and the organic phase was dried with anhydrous magnesium sulfate for 12 hours. The ethyl acetate was then removed by rotary evaporation and vacuum dried at 60°C for 24 hours to obtain the desired first-step intermediate VD.
[0050] (2) In a three-necked round-bottom flask, VD was dissolved in anhydrous ethanol. Subsequently, Pramine 1074 was added to the above solution and refluxed at 70°C for 4 h. The solvent was removed by rotary evaporation and then vacuum dried at 70°C for 24 h to obtain the desired Schiff base intermediate VDP.
[0051] (3) Add 15 parts of the prepared VDP to 100 parts of bisphenol A epoxy resin, stir evenly at 90°C and evacuate. When there are no bubbles in the mixture in the vacuum, add 25 parts of molten 4,4-diaminodiphenylmethane (DDM) as a curing agent at 105°C and mix evenly. Pour the mixed sample into the mold quickly, preheat the mold at 110°C for 30 min, cure at 120°C for 2h, adjust the temperature to 150°C, and post-cure for 2h to obtain the epoxy composite material 15VDP.
[0052] The bending strength, elongation at break, impact strength and flame retardancy of the epoxy composite materials prepared in the above six embodiments and two comparative examples were tested, and the data results are shown in Table 1. The tensile stress-strain curves of the epoxy composite materials in Embodiments 1-3 and Comparative Examples 1-2 are shown in Table 1. Figure 2 , the comparison chart of bending strength and bending modulus is shown in Figure 3 , impact strength comparison chart see Figure 4 . It can be proved that the -NH group in the flame retardant successfully participates in the curing reaction of the epoxy resin, cross-links with the epoxy resin to form a special network structure, and greatly improves the compatibility of the flame retardant and the epoxy resin. The rigid groups and flexible chains in the flame retardant cooperate with each other to give the epoxy resin matrix excellent mechanical properties. Therefore, the epoxy composite material prepared by the present invention has significantly improved bending strength, elongation at break, impact strength, and flame retardant properties compared to ordinary E51 epoxy resin materials, and has also been improved compared to the Schiff base epoxy composite material in Comparative Example 2.
[0053] Table 1
Claims
1. A bio-based double P flame retardant, characterized in that: The structural formula is as follows: ; In the formula, R1 is selected from , , , , , One of; R2 is selected from , , , , One of the following, wherein n1 is any integer from 1 to 16, and n2 is selected from 230, 400, 600, 1000 or 2000.
2. A method for preparing the bio-based double P flame retardant according to claim 1, characterized in that: The steps include: Step 1: dissolving raw material A and triethylamine in ethyl acetate, then adding diphenyl chlorophosphate dropwise at 0°C to 5°C under a nitrogen atmosphere, stirring for 30min to 60min, gradually warming the system to room temperature and continuing stirring for 12h to 24h, and then performing post-treatment to obtain the first intermediate; Step 2: dissolving the intermediate obtained in the first step in a solvent, then adding raw material B, and reflux reacting at 30°C~90°C for 2h~10h. After the reaction is completed, removing the solvent by rotary evaporation, and then vacuum drying at 50°C~80°C for 12h~24h to obtain a Schiff base intermediate; Step 3, dissolving the prepared Schiff base intermediate in a solvent, then dropping DOPO under a nitrogen atmosphere, and reflux reacting at 50°C to 120°C for 8h to 20h. After the reaction, removing the solvent by rotary evaporation, and then vacuum drying at 50°C to 100°C for 12h to 24h to obtain a bio-based double P flame retardant; Wherein, the raw material A is selected from one or a combination of at least two of vanillin, p-hydroxybenzaldehyde, 5-hydroxymethylfurfural, salicylaldehyde, protocatechualdehyde, and syringaldehyde; The raw material B is selected from one or a combination of at least two of Pramine 1074, diethylenetriamine, triethylenetetramine, 1,5-pentanediamine, 1,6-hexanediamine, polyetheramine D-230, polyetheramine D-400, polyetheramine D-600, polyetheramine D-1000, and polyetheramine D-2000.
3. The method for preparing the bio-based double P flame retardant according to claim 2, characterized in that: The post-treatment method includes: suction filtration, washing, drying and rotary evaporation.
4. The method for preparing the bio-based double P flame retardant according to claim 2, characterized in that: The solvent in step 2 is one or a combination of at least two of anhydrous ethanol, methanol, tetrahydrofuran, dichloromethane, chloroform, ethyl acetate, acetone, toluene, and 1,4-dioxane.
5. The method for preparing the bio-based double P flame retardant according to claim 2, characterized in that: The solvent in step three is one or a combination of at least two of methanol, anhydrous ethanol, acetone, toluene, 1,4-dioxane, and N,N-dimethylformamide.
6. An epoxy composite material, characterized in that: The raw materials include, by weight: 1-20 parts of the bio-based double P flame retardant according to claim 1, 100 parts of epoxy resin, and 25 parts of curing agent.
7. The epoxy composite material according to claim 6, characterized in that: The epoxy resin is bisphenol A epoxy resin, and the curing agent is 4,4'-diaminodiphenylmethane.
8. A method for preparing the epoxy composite material according to claim 6 or 7, characterized in that: The steps include: The bio-based double P flame retardant and epoxy resin are stirred and mixed at 70° C. to 120° C., and a uniform system is obtained and then vacuumed. When there are no bubbles in the mixture in the vacuum, a curing agent is added at 50° C. to 120° C. and mixed uniformly. Finally, the mixture is poured into a preheated mold for curing.
9. The method for preparing the epoxy composite material according to claim 8, characterized in that: The mold preheating temperature is 80°C to 120°C, and the preheating time is 30min to 90min; the curing process is specifically as follows: after curing at 100°C to 140°C for 60min to 120min, the temperature is adjusted to 120°C to 160°C, and then cured for 60min to 150min.
10. Use of the epoxy composite material according to claim 6 or 7, characterized in that: Used for the preparation of the winding layer of Type IV fully wound hydrogen storage cylinders.
Citation Information
Patent Citations
Syringaldehyde group epoxy resin with Schiff base structure and preparation method of syringaldehyde group epoxy resin
CN115093544A
Syringaldehyde-based intrinsic flame-retardant epoxy curing agent and preparation method of syringaldehyde-based intrinsic flame-retardant epoxy curing agent resin
CN116284137A
Durable flame-retardant finishing method for polyester / cotton blended fabric
CN116905224A